Finite-Time Control of Wing-Rock Motion for Delta Wing Aircraft Based on Whale-Optimization Algorithm - Arif A. Al-Qassar; Abdulkareem Sh. Mahdi Al-Obaidi; Alaq F. Hasan; Amjad J. Humaidi; Ahmed R. Nasser; Ahmed Alkhayyat; Ibraheem Kasim Ibraheem (Universitas Pendidikan Indonesia, 2021)
The rise of wing-rock motion in delta-wing aircraft has an adverse effect on the manoeuvrability of aircraft and it may result in its crash. This study presents a finite-time control design to tackle the dynamic motion due to the Wing-Rock effect in delta-wing aircraft. The control design is developed based on the methodology of Super Twisting Sliding Mode Control (STSMC). The Lyapunov stability analysis has been pursued to ensure asymptotic convergence of errors and to determine the finite time. The design of STSMC leads to the appearance of design parameters, which have a direct impact on the dynamic performance of the controlled system. To avoid the conventional tuning of these parameters and to have an optimal performance of the proposed controller, a modern optimization technique has been proposed based on Wale Optimization Algorithm. A comparison study between optimal and non-optimal finite-time super twisting sliding mode controllers has been established and their effectiveness has been verified via numerical simulation using MATLAB programming format.